FILM DOKUMENTER â€œHIROSHIMA: DROPPING BOMBâ€ INOVASI PEMBELAJARAN PENDIDIKAN KREATIF? - Mulyani, Santi Vera; Selvia, Belva; Lianti, Desi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstractâ€” Various information obtained by students is no longer fully obtained from the teacher but also from search engines like Google, Youtube applications and so on. This true picture is more easily obtained by students from elementary, junior high to senior high schools in this disruptive era encouraging teachers to utilize the technology as innovative learning in creative education. Real images of events in the past for example become critical questions in the era of openness as it is now encouraging writers to conduct research. Besides the lack of motivation to learn students on the subject of nationalism is also a driving force for writers. The purpose of this study was to determine the description of the use of the documentary film media "Hiroshima" as a supporter of historical learning on the subject of the roots of nationalism for class XI IPS students at SMA Negeri 1 Muara Sugihan. This study uses a qualitative research methodology with a literature study and documentation data collection method. The results of the study show that there is a benefit for the use of the documentary film media "Hiroshima" as a supporter of historical learning on the subject of nationalism roots for students of class XI IPS in SMA Negeri 1 Muara Sugihan, which is expected to be used in other subjects and even in other subjects and at levels. other education such as in elementary, junior high to high school, remembering that documentary films are very supportive in contextual and conceptual learning.Keywordsâ€” Documentary film, Hiroshima, learning innovation Â Abstrakâ€” Berbagai informasi yang diperoleh peserta didik tidak lagi didapat sepenuhnya dari sosok guru tapi juga dari mesin pencari seperti Google, aplikasi Youtube dan sebagainya. Gambaran nyata ini semakin mudah didapatkan peserta didik dari SD, SMP hingga SMA pada era disruptif ini mendorong para guru untuk memanfaatkan teknologi tersebut sebagai inovasi pembelajaran pendidikan kreatif. Gambaran nyata tentang peristiwa di masa lalu misalnya menjadi pertanyaan yang kritis di era keterbukaan seperti sekarang mendorong penulis melakukan penelitian. Selain itu kurangnya motivasi belajar siswa pada pokok bahasan nasionalisme juga menjadi pendorong penulis. Tujuan penelitian ini adalah untuk mengetahui gambaran pemanfaatan media film dokumenter â€œHiroshimaâ€ sebagai pendukung pembelajaran sejarah pokok bahasan akar-akar nasionalisme bagi siswa kelas XI IPS di SMA Negeri 1 Muara Sugihan. Penelitian ini menggunakan metodologi penelitian kualitatif dengan metode pengumpulan data studi pustaka dan dokumentasi. Hasil penelitian menunjukkan adanya manfaat atas penggunaan media film dokumenter â€œHiroshimaâ€ sebagai pendukung pembelajaran sejarah pokok bahasan akar-akar nasionalisme bagi siswa kelas XI IPS di SMA Negeri 1 Muara Sugihan diharapkan dapat digunakan dalam pokok bahasan lain dan bahkan dalam mata pelajaran lain dan pada jenjang pendidikan lain seperti di SD, SMP hingga SMA mengingat film dokumenter sangat mendukung dalam pembelajaran yang kontekstual dan konseptual.Kata Kunciâ€” Film dokumenter, Hiroshima, inovasi pembelajaran